THE EFFECT OF OXYTOCIN MASSAGE ON BREAST MILK PRODUCTION AMONG BREASTFEEDING WOMEN AT RB CITRA LESTARI BOJONGGEDE BOGOR IN 2022 - Hayuningsih, Sri; Kusmintarti, Arini (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Efforts to support the increase in exclusive breastfeeding can be seen by the issuance of various recognitions or agreements, both global and national in nature, which aim to protect, promote and support breastfeeding for every baby throughout the world to obtain their right to breast milk. In Indonesia, infants who received exclusive breastfeeding in 2020 amounted to 69.62%. The Ministry of Health (KemKes) has set a target of 80% exclusive breastfeeding coverage every 2020-2024. To determine the effect of breast milk production before and after oxytocin massage at TPMB Bersama Citra Lestari Bojonggede, Bogor Regency, in 2022.Using pre-experimental with One Group PreTest-Posttest Designs research design. This study's sample number was 20 respondents with an accidental sampling technique that met the inclusion criteria. Shapiro Wilk carried out the normality test and found that the data were not normally distributed. Data analysis using a non-parametric test with Wilcoxon Signed Rank Test. The research results were conducted by pre-testing 20 respondents were breastfeeding women before oxytocin massage. Most of the milk production was less than 11 (55%). While the breast milk production after oxytocin massage is as sufficient as 12 (60%). It can be concluded that if the p value= 0.000 < (0.05), Ho is rejected, and Ha is accepted. The conclusion of this study is the significant effect of oxytocin massage on breast milk production at RB Citra Lestari Bojonggede Bogor in 2022.